Implementasi Pembelajaran Berbasis Metode Discovery Learning Pada Mapel Akidah Akhlak di MTSs Nurul Qomar Pekalongan - Faiqotul Mutia; Fatmawati Nur Hasanah; Arditya Prayogi (Global Sustainability Research Institute, 2025)
Introduction: Using interesting and fun learning methods will greatly affect the learning atmosphere in the classroom. To overcome this, a teacher's strategy is needed in the learning process, namely by applying an appropriate learning method or model to maintain a good learning process. One of them is by using the discovery learning learning model. Methods: This research is a type of qualitative research supported by data collection methods by means of observation, interviews, and documentation. Results: The study found that the implementation of discovery learning in the subject of aqidah morals at MTs Salafiyah Nurul Qomar Pekalongan involved three main stages. First, the planning stage included preparing lesson plans, syllabus, and handbooks to ensure material readiness. Second, the implementation stage consisted of three phases: the preliminary phase, where teachers greeted students, conveyed objectives, and conducted apperception; the content phase, involving stimulation, problem identification, data collection, data processing, proof, and generalization; and the closing phase, where teachers appreciated student performance and provided motivational closure. Third, the evaluation stage showed the model's success, as indicated by students' improved grades. Conclusion and suggestion: The use of discovery learning methods in learning can improve the learning process of students in terms of knowledge, attitudes, and motor skills providing a broad understanding. For this reason, the discovery learning model needs to be consistently applied so that students can think critically, find new discoveries, and get used to examining problems.